Lung Clearance Index in Children with Cystic Fibrosis during Pulmonary Exacerbation - Katarzyna Walicka-Serzysko (MDPI AG, 2021)
(1) Background: Pulmonary exacerbation (PEx) is one of the main factors affecting the quality of life and life expectancy in patients with cystic fibrosis (CF). Our study aimed to evaluate the change in selected pulmonary function parameters, including lung clearance index (LCI), in patients with CF diagnosed with PEx. (2) Methods: We enrolled 40 children with CF aged 6–17. They performed spirometry and multiple breath nitrogen washout (MBNW) tests during a stable condition period at the beginning and the end of intravenous antibiotic treatment. (3) Results: LCI increased by 65% and FEV1 decreased by ≥10% in 40% of patients with CF during PEx. An absolute change in LCI between a stable condition period and PEx was 1.05 (±1.92) units, which corresponds to a relative change of 11.48% (±18.61) of the baseline. The relative decrease in FEV1 was −9.22% (±12.00) and the z-score was −0.67 (±1.13). After the PEx treatment, FEV1 increased by 11.05% (±9.04) on average, whereas LCI decreased by 1.21 ± 1.59 units on average, which represented 9.42% ± 11.40 compared to the value at the beginning of PEx. (4) Conclusions: The change in LCI captures a higher proportion of events with functional impairment than FEV1 in school-age children with CF.